The effect of self-determination skills training on Academic Vitality and Academic Hope - zahra tabatabaee; Ahmad Abedi; Ghasem Norouzi (مطالعات روانشناسی تربیتی)
The aim of this study was to investigate the effect of self-determination skills training on academic vitality and academic hope in underachievement gifted students. This study was a quasi-experimental study with pretest-posttest design and control group. The study population of the present study included underachievement gifted students in Shahroud. The sample consisted of 30 underachievement gifted students who were selected by judicative sampling method and randomly and equally assigned to the experimental and control groups (15 people in each group). The experimental group participated in a self-determination skills training program that was conducted in 8 sessions of 50 minutes (one session per week), while the control group did not participate in this program. Participants were assessed using the Academic Vitality Questionnaire (2012) and the Academic Hope Questionnaire (2001). Data were analyzed using univariate and multivariate analysis of covariance. The results of analysis of covariance showed that self-determination skills training had a positive and significant effect on academic vitality and academic hope of underachievement gifted students (P <0.05). it can be concluded from the findings of this study that self-determination skills training has an effect on the vitality and academic hope of underachievement gifted students. Therefore, this method can be used in the educational and rehabilitation program of this group of children.